Fabrication of PES/PVP Water Filtration Membranes Using Cyrene®, a Safer Bio-Based Polar Aprotic Solvent - Roxana A. Milescu; C. Robert McElroy; Thomas J. Farmer; Paul M. Williams; Matthew J. Walters; James H. Clark (Advances in Polymer Technology)
A more sustainable dialysis and water filtration membrane has been developed, by using the new, safer, bio-based solvent Cyrene® in place of N-methyl pyrrolidinone (NMP). The effects of solvent choice, solvent evaporation time, the temperature of casting gel, and coagulation bath together with the additive concentration on porosity and pore size distribution were studied. The results, combined with infrared spectra, SEM images, porosity results, water contact angle (WCA), and water permeation, confirm that Cyrene® is better media to produce polyethersulfone (PES) membranes. New methods, Mercury Intrusion Porosimetry (MIP) and NMR-based pore structure model, were applied to estimate the porosity and pore size distribution of the new membranes produced for the first time with Cyrene® and PVP as additive. Hansen Solubility Parameters in Practice (HSPiP) was used to predict polymer-solvent interactions. The use of Cyrene® resulted in reduced polyvinylpyrrolidone (PVP) loading than required when using NMP and gave materials with larger pores and overall porosity. Two different conditions of casting gel were applied in this study: a hot (70°C) and cold gel (17°C) were cast to obtain membranes with different morphologies and water filtration behaviours.